An evaluation of students’ practical intelligence and ability to diagnose equipment faults - Zol Bahri, Razali, Dr.; Trevelyan, James P. (Universiti Teknologi Malaysia (UTM), 2013)
Proceedings of the 3rd Regional Conference on Engineering Education (RCEE 2010) was organized by Universiti Teknologi Malaysia (UTM), 6th - 9th June 2010 at Kuching, Sarawak, Malaysia.